Measurements of Rayleigh–Taylor instability growth of laser-shocked iron–silicon alloy. Issue 1 (2nd January 2019) - Sakaiya, Tatsuhiro; Terasaki, Hidenori; Akimoto, Kosaku; Kato, Hiroki; Ueda, Taichi; Hosogi, Ryota; Fujikawa, Takashi; Kondo, Tadashi; Hironaka, Yoichiro; Shigemori, Keisuke
ABSTRACT: The Rayleigh–Taylor (RT) instability of liquid iron alloys is important for understanding the core formation mechanism in the Earth. Here we first report the measurement of RT instability growth for a liquid iron–silicon (Fe–Si) alloy, which is one of the major candidate for the material of the Earth's core, using a high power laser. We optimized the measurement setup and analytical technique to observe the growth of perturbation on an Fe–Si sample surface. The growth of perturbation amplitude on the Fe–Si alloy under high pressure and temperature was successfully observed using in situ X-ray radiography. The growth rate of the RT instability for the Fe–Si alloy on about 1000 GPa was estimated to be 0.3 ns −1 .